Undang-Undang Sumatera Barat (Minangkabau) Tahun 1837-1862 - Yulianti yulianti; Amung Ahmad Syahir Muharam; Fathia Lestari (UIN Sunan Gunung Djati Bandung, 2020)
This article discusses the constitution (undang-undang) of West Sumatra. The Minangkabau people constitute the Matrilineal community. Their customs and culture place the women as the inheritors of inheritance and kinship. Nevertheless, the role of men who actively play roles in religious and political spheres is still significant. Seen from their economy, the Minangkabau indigenous people have a wealth of fertile land so that the majority of the community's work is farming various plants such as coffee, spices, rice etc. The progress of the community is not only in the economic field but also the development of Islam. The spread of Islam continues to grow and the Islam has been a popular religion among the Minangkabau people. The community also has a legal order written in an Act, which was written in Minangkabau in 1837 precisely after the Padri war and the Dutch rule in the Minangkabau land. Dutch Residents (Heinmers) ordered community leaders to write a customary law into the West Sumatra Act, the enactment of this West Sumatra Law until 1862 because when the Dutch set new regulations on the Minangkabau community, namely stelsel culture so that people followed all the new rules. The West Sumatra Law is divided into three parts: the Adat Law in Nagari, the Murder Case Law, and the Syara Companding Adat Law. Keywords: Minangkabau Society, customary law, local act.